Coordination as Management Response to the Spread of a Global Plant Disease: A Case Study in a Major Philippine Banana Production Area - Montiflor, Marilou O.; Vellema, Sietze; Digal, Larry N. (Frontiers in Plant Science, 2019)
An integrative management approach to the spread and emergence of global plant diseases, such as the soil-borne fungus Fusarium oxysporum f. sp. cubense tropical race 4 (Foc TR4), entails a combination of technical measures and the responsiveness and awareness of area-specific constellations supporting conditions conducive to interactions and coordination among organizations and actors with different resources and diverse interests. Responses to banana diseases are mostly studied through technical and epidemiological lenses and reflect a bias to the export industry. Some authors, however, indicate that cross-sector collaboration is crucial in responding to a disease outbreak. Earlier studies on the outbreak of diseases and natural disasters suggest that shared cognition and effective partnerships increased the success rate of response. Hence, it is important not to focus exclusively on the impacts of a pathogen at farm or field level and to shift attention to how tasks and knowledge are coordinated and shared. This paper aims to detect whether and how the emergence of Foc TR4 is a driver of coordination. The case study focuses on the interactions between a variety of banana producers and among a range of public and private actors in southern Philippines. The analysis identifies distinct forms of coordination emerging in the context of three organizational fields responding to Foc TR4, which underlie shared capacity to handle and understand the spread of a global plant disease. The research is based on qualitative key informant interviews and document analysis and on observations of instructive events in 2014–2017. Analysis of the composition and actions developed in three organizational fields leads to distinguishing three theory-driven forms of coordination: rule-based, cognition-based, and skill-based. The combination of these three forms constitutes the possibility of a collaborative community, which conditions the implementation of an integrative management approach to mitigate Foc TR4.